Column layout design for concrete frame structures utilizing the strain energy-based topology optimization method - Xin-Cai Xiong; Hu-Zhi Zhang; Gang Peng; Fei-Fan Feng (Journal of Asian Architecture and Building Engineering)
Intelligent design is advancing civil engineering, providing new opportunities for structural optimization.This paper proposes an innovative intelligent design method integrating topology optimization into concrete frame column layout design.The method iteratively removes a defined percentage of columns from the initial layout, guided by the architectural plan, to achieve optimal column topologies.The approach’s efficacy is validated through a numerical example and a practical case study, showing that materials in optimized frames enhance structural stiffness more effectively than in traditional designs. Structures optimized via topology optimization can reduce material usage by 16% to 18% while preserving material properties.Moreover, comparing optimized designs at varying target volume fractions shows that initial fractions between 0.6 and 0.8 yield structures with robust performance and adequate stiffness.Thus, optimized column layouts allow structures to achieve maximum stiffness with fixed material or minimal material for specific stiffness requirements. Furthermore, the automated process enhances design efficiency and logic, reducing reliance on designer subjectivity. This method improves structural design efficiency, performance, and material conservation.